Dynamic high-resolution ultrasound of intrinsic and extrinsic ligaments of the wrist: How to make it simple. Issue 87 (February 2017) - Gitto, Salvatore; Messina, Carmelo; Mauri, Giovanni; Aliprandi, Alberto; Sardanelli, Francesco; Sconfienza, Luca Maria
Highlights: US allows for rapid, cost-effective, and non-invasive assessment of wrist ligaments. Knowledge of landmarks and dynamic manoeuvres is basic for a systematic examination. A sequential approach is effective, timesaving and feasible in clinical practice. Abstract: Wrist ligaments are crucial structures for the maintenance of carpal stability. They are classified into extrinsic ligaments, connecting the carpus with the forearm bones or distal radioulnar ligaments, and intrinsic ligaments, entirely situated within the carpus. Lesions of intrinsic and extrinsic ligaments of the wrist have been demonstrated to occur largely, mostly in patients with history of trauma and carpal instability, or rheumatoid arthritis. Ultrasound allows for rapid, cost-effective, non-invasive and dynamic evaluation of the wrist, and may represent a valuable diagnostic tool. Although promising results have been published, ultrasound of wrist ligaments is not performed in routine clinical practice, maybe due to its technical feasibility regarded as quite complex. This review article aims to enlighten readers about the normal sonographic appearance of intrinsic and extrinsic carpal ligaments, and describe a systematic approach for their sonographic assessment with detailed anatomic landmarks, dynamic manoeuvres and scanning technique.